Competent enough to be heard? Technicians’ expectations about local stakeholders in participative processes - Lima, M. L.; Marques, S.; Branco, C.; Talayero, F.; Camilo, C. (Applied Psychology: An International Review, 2018)
The involvement of citizens in environmental decision processes is difficult to implement, and little is known about the psychological mediators for the technicians’ resistance. We tested the hypothesis that the subtle denial of human attributes of local stakeholders (dehumanisation) produces negative expectations regarding the engagement of communities in the decision process, which may ultimately legitimise their exclusion. Three studies were conducted testing this hypothesis, all involving professionals with experience in implementing local projects. In the first two correlational studies we showed that a deficit view regarding local communities, a dehumanised idea of those residents and an unfavourable attitude towards their participation were associated. Furthermore, an experimental study was conducted, manipulating the images of the residents in a 2 warmth (high vs low) × 2 competence (high vs low) between-subjects design. Results showed that participants that read a description of the local community as being incompetent developed expectations of more violent and less conventional forms of protest. Moreover, the expectation of conventional protest procedures was associated with stronger support for their engagement in the process. These studies show the importance of psychosocial mediators from the technicians’ perspective: an imagined competent public is easier to include in the decision process.